2015
DOI: 10.1002/hbm.22920
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation of resting state functional connectivity, striatal GABA levels, and cognitive control processes

Abstract: Important issues for cognitive control are response selection processes, known to depend on fronto-striatal networks with recent evidence suggesting that striatal gamma-amino butyric acid (GABA) levels play an important role. Regional GABA concentrations have also been shown to modulate intrinsic connectivity, e.g. of the default mode network. However, the interrelation between striatal GABA levels, basal ganglia network (BGN) connectivity, and performance in cognitive control is elusive. In the current study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…While this is increasingly recognized in the literature (Becker et al, 2018;Haag et al, 2015;Mahjoory et al, 2019;Tavor et al, 2016), the current study is the first to show this for the theta band oscillations in the context of inhibitory control. Notably, the data analysis of the PLF in Nogo trials revealed no differential effects between the high baseline group and the low baseline group, which was confirmed by Bayesian statistics.…”
Section: Resting Theta Activity Groupingsupporting
confidence: 51%
See 2 more Smart Citations
“…While this is increasingly recognized in the literature (Becker et al, 2018;Haag et al, 2015;Mahjoory et al, 2019;Tavor et al, 2016), the current study is the first to show this for the theta band oscillations in the context of inhibitory control. Notably, the data analysis of the PLF in Nogo trials revealed no differential effects between the high baseline group and the low baseline group, which was confirmed by Bayesian statistics.…”
Section: Resting Theta Activity Groupingsupporting
confidence: 51%
“…In line with overarching theoretical conceptions concerning the function of the medial frontal cortex and theta band activity (Cavanagh & Frank, 2014), the increase in theta band power in Nogo trials has been suggested to reflect an "alarm" or "surprise signal," which is crucial for increasing cognitive control Dippel et al, 2017;Wessel, 2018). On the other hand, it is increasingly recognized that there are similarities between resting dynamics and activity related to cognitive control (Becker, Van de Ville, & Kleinschmidt, 2018;Haag et al, 2015;Mahjoory, Cesnaite, Hohlefeld, Villringer, & Nikulin, 2019;Tavor et al, 2016). Based on these findings, it could be assumed that the individual ability to increase theta activity beyond a certain resting state activity is essential for successful response inhibition performance.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In the results section, the mean and standard errors of the mean (SEM) are reported as a measure of variance. MRS data were integrated with the behavioral and neurophysiological data by means of correlation [19,63,83,84]. For this, the individual GABA and glutamate concentrations in the ACC and striatum at baseline (i.e., in the sober state) were used to predict the behavioral differences between sober and intoxicated (i.e., sober-intoxicated) appointments for each combination of experimental conditions.…”
Section: Statisticsmentioning
confidence: 99%
“…Karayanidis et al ; Gehring et al ; Gajewski et al ) are reflected by the N2 ERP originating from the anterior cingulated cortex (ACC) (Folstein and Van Petten ). As these mechanisms represent important cognitive subprocesses during task switching (Gajewski et al ; Gajewski et al ) and are subject to modulation by the dopamine and the GABAergic system (Stock et al ; Steenbergen et al ; Haag et al ; Quetscher et al ; Beste et al ), these processes may be particularly affected by high‐dose ethanol intoxication and hangover. Furthermore, processes relating to updating of working memory processes, which are indexed by the P3 ERP (Polich and Kok ; Barceló ; Polich ) and are also strongly involved in memory‐based task switching, may be affected as well.…”
Section: Introductionmentioning
confidence: 99%